Effect of Seedling Size on the Growth of Transplanted Spruce Seedlings in the Nursery - Singh, Ombir; Bhagat, S.; Chaukiyal, S. P. (Indian Forester, 1988)
An experiment was undertaken to study the effect of seedlings size on the growth of transplanted spruce seedlings in the nursery. Studies made include observations on survival and growth of seedlings under five different classes based on their hieghts viz. less than 7.5 cm; 7.5 cm to < 12.5 cm; 12.5 cm to < 17.5 cm; 17.5 cm to 22.5 cm and more than 22.5 cm. The performance of the seedlings below 7.5 cm in height in terms of both survival and growth was the poorest as compared to all other classes followed by the seedlings of 7.5 cm -< 12.5 cm height classes which also resulted in lower survival and poorer growth rate than those of the remaining three classes. Seedlings below 12.5 cm in height should, therefore, be culled at the time of transplanting.